Integrated Marketing Communication Strategy After Pandemi Through Instagram Social Media On @Pathis_Chocolade Account - Amerta, Jasmin Nabila; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2024)
The business world in various fields continues to increase and experiences very rapid development, one of which is business in the food sector. Supported by the presence of new media which can be a forum for implementing digital marketing strategies, businesses in the food sector can generate large profits. Therefore, the aim of this research is to analyze Pathis Chocolade's integrated marketing communications strategy through social media Instagram @pathis_chocolade. This type of research uses descriptive qualitative methods. The subject in this research is the Pathis Chocolade Instagram account with the username @pathis_chocolade as well as the primary data source for this research. Secondary data was taken through references to journals, books, e-books, articles and websites. Observation and interviews are data collection techniques in this research. Based on the results of this research, Pathis Chocolade involves an Integrated Marketing Communication strategy through Instagram social media, namely Advertising, Direct Marketing, Personal Selling, Sales Promotion, Public Relations, Sponsorship, Experiential Marketing, Social Media Marketing, and Word Of Mouth Marketing. The strategies that Pathis Chocolade often uses are Sales Promotion and Sponsorship because these two strategies get relatively more audience attention than other strategies. However, there are strategies that Pathis Chocolade has not implemented, namely Brand, Green Marketing, Electronic Marketing and Relationship Marketing.